Vitamin D3 Activates Phosphatidylinositol-3-Kinase/Protein Kinase B via Insulin-Like Growth Factor-1 to Improve Testicular Function in Diabetic Rats. (4th June 2019) - He, Yanyan; Liu, Yang; Wang, Qing-Zhu; Guo, Feng; Huang, Fengjuan; Ji, Linlin; An, Tingting; Qin, Guijun
Abstract : Objective . In diabetes mellitus, vitamin D3 deficiency affects sex hormone levels and male fertility; however, the mechanism leading to the disorder is unclear. This research was designed to investigate the mechanism of vitamin D3 deficiency and hypogonadism in diabetic rats. Our aim was to assess serum vitamin D3 levels and the relationship among vitamin D3, insulin-like growth factor-1 (IGF-1), and testicular function. Materials and Methods . Rats with streptozotocin-induced diabetes were randomly divided into four groups and treated with different doses of vitamin D3 : no vitamin D3, low (0.025 μ g/kg/day), high (0.1 μ g/kg/day), and high (0.1 μ g/kg/day) with JB-1 (the insulin-like growth factor-1 receptor inhibitor group, 100 μ g/kg/day). The groups were compared with wild-type rats, which function as the control group. Various parameters such as vitamin D3 and IGF-1 were compared between the experimental and wild-type groups, and their correlations were determined. Results . Twelve weeks of vitamin D3 supplementation improved the testosterone levels, as shown by the increase in the level of serum IGF-1 in diabetic rats. Phosphatidylinositol-3-kinase (PI3K)/protein kinase B (AKT), which was a downstream of the signaling pathway of IGF-1, was significantly increased after vitamin D3 treatment. Conclusions . The study shows that vitamin D3 may promote the expression of testosterone and improve testicular function in diabetic rats by activating PI3K/AKT via IGF-1.